Changes in the sodium content of leading Australian fast‐food products between 2009 and 2012. Issue 6 (7th April 2014) - Garcia, Julianne; Dunford, Elizabeth K; Sundstrom, Johan; Neal, Bruce C
Abstract: Objective: To define the changes in sodium levels of Australian fast foods between 2009 and 2012 overall, in major food subcategories and by company. Design: A comparison of mean sodium content was made across 4 years using t tests and mixed models. Setting: Nutrient content data for fast‐food menu items collected from company websites of six large Australian fast‐food chains. Main outcome measures: Mean sodium values in mg/100 g and mg/serve. Results: There were between 302 and 381 products identified each year. Overall, the mean sodium content of fast‐food products decreased between 2009 and 2012 by 43 mg/100 g (95% CI, − 66 to − 20 mg/100 g), from 514 mg/100 g in 2009 to 471 mg/100 g in 2012. Mean sodium content per serving was not significantly different at 654 mg in 2009 and 605 mg in 2012 (− 49 mg; 95% CI, − 108 to + 10 mg), reflecting wide variation in the serving sizes of items offered each year. There was a small decline in sodium content over the 4 years across most food categories and food companies. Conclusions: The observed reduction in the sodium content of fast foods during the 4‐year study period is encouraging. However, the reductions are small, and fast‐food companies should be encouraged to make further and larger reductions since many products still contain high levels of sodium.